Identification of a Novel EF-Loop in the N-terminus of TRPM2 Channel Involved in Calcium Sensitivity - Luo, Yuhuan; Yu, Xiafei; Ma, Cheng; Luo, Jianhong; Yang, Wei (Frontiers in Pharmacology, 2018)
As an oxidative stress sensor, transient receptor potential melastatin 2 (TRPM2) channel is involved in many physiological and pathological processes including warmth sensing, ischemia injury, inflammatory diseases and diabetes. Intracellular calcium is critical for TRPM2 channel activation and the IQ-like motif in the N-terminus has been shown to be important by mediating calmodulin binding. Sequence analysis predicted two potential EF-loops in the N-terminus of TRPM2. Site-directed mutagenesis combining with functional assay showed that substitution with alanine of several residues, most of which are conserved in the typical EF-loop, including D267, D278, D288 and E298 dramatically reduced TRPM2 channel currents. By further changing the charges or side chain length of these conserved residues, our results indicate that the negative charge of D267 and the side chain length of D278 are critical for calcium-induced TRPM2 channel activation. G272I mutation also dramatically reduced the channel currents, suggesting that this site is critical for calcium-induced TRPM2 channel activation. Furthermore, D267A mutant dramatically reduced the currents induced by calcium alone compared with that by ADPR, indicating that D267 residue in D267-D278 motif is the most important site for calcium sensitivity of TRPM2. In addition, inside-out recordings showed that mutations at D267, G272, D278 and E298 had no effect on single-channel conductance. Taken together, our data indicate that D267-D278 motif in the N-terminus as a novel EF-loop is critical for calcium-induced TRPM2 channel activation.